The Influence of Inquiry Models With a STEM Approach on Critical Thinking Ability in Low-Level Plant Structure Courses - Ivan Eldes Dafrita; Nawawi Nawawi (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
The critical thinking ability of prospective biology teacher students still needs to be improved to support the implementation of 21st century learning in schools. This study aims to determine the effectiveness of the STEM-based Inquiry learning model on critical thinking skills in the Low-Level Plant Structure course. This research is a type of pseudo-experimental research, using control group Pretest-Posttest Design, involving 50 students who are divided into two classes, namely the control class and the experimental class. The data collection tools used in this study were student response questionnaires, critical thinking skills tests. Data analysis, researchers conducted testing using SPSS software. The results of data analysis obtained from the t-test of paired samples were obtained Sig. 0.00 < 0.005, which can be interpreted that there is a significant difference in effectiveness between critical thinking skills in experimental classes using STEM-based Inquiry and control classes using Inquiry in the Low-Level Plant Structure course. So it can be concluded that there is a positive and significant influence from the use of STEM-based inquiry on the critical thinking ability of prospective teacher students in the Biology Education Study Program